MASYARAKAT DAN KEBUDAYAAN SEKOLAH - Normina, Normina (STAI AL FALAH Banjarbaru, 2018)
The community is a community that interdependent (interdependence with each other). Generally, the term is used to refer to a group of community people who live together in one community that regularly. From birth to death human life as members of the community. Human beings always have a strong instinct to live together. Mix for quite a long time. They are aware that they are a single entity, and they constitute a system of living together. System life together is, therefore, culture inflict, every Member feels tied to one another. When compared with other living things as animals, for example, human life would not be possible on its own. Humans without other human are sure to die, the man locked up alone in a closed room, would be disrupted on his personal development, so that eventually he will die. The culture of the school is the education system certain behavior patterns develop in accordance with what is expected by the community and the students. Life at school as well as the norms that apply in situ can be called with the Culture of the school. The school culture is habits, values, norms, rituals, myths, formed in the course of long held together by school principals, teachers, administrative staff, and students as their basis in understanding and solving a wide range of issues that arise in school. Keywords: community, change, culture, school.